Green Synthesis Silver Nanparticles Using and Rographis Paniculata (nees) and its Antimicrobial Activity against Human Pathogens - K Vijayakumar; G Thiruneelakandan (Journal of Global Pharma Technology, 2018)
In the present examination, an undertaking was made to nanoparticle by using a remedially fundamental plant Andrographis panticulata. The applications plant materials which would help in the neutralizing activity of human pathogens. Silver nitrate (AgNO3) was used to coordinate the silver nanoparticle by using leaves focus of A. paniculata was used as a diminishing and offsetting administrator. The organized silver nanoparticles from 1mM AgNo3 game plan through the leaves expel were depicted using UV-VIS spectrophotometry, Scanning Electron Microscope (SEM) and Fourier Transform Infra-Red (FTIR). The nanoparticles should remarkable antimicrobial activity against multi-sedate safe human pathogenic sorts of the two tiny living beings and Fungi (Bacillus subtilis, Escherichia coli, Klebsiella pneumonia, Proteus mirabilis, Streptococcus fecalis, Aspergillus conicus, Aspergillus flavus, Aspergillus niger, Aspergillus terreus and Rhizopus. sp). The result reveals that the most outrageous antimicrobial activity was seen against the test life frame when stood out from the control.Keywords: Silver nanoparticles, Andrographis paniculata, SEM, UV-VIS spectroscopy, FT-IR, Antimicrobial activity.